EVALUATION OF THE PROTOTYPING METHOD IMPLEMENTATION IN MOBILE APPLICATION DEVELOPMENT FOR MATERNAL HEALTH MONITORING - Anggy Trisnadoli; Indah Lestari; Desy Winda; Mona Dewi Utari (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The advancement of technology has transformed the health sector, enabling efficient and accessible health monitoring through digital platforms. To support pregnancy monitoring, a mobile-based user experience (UX) design for the BiBu Mobile Health Monitoring Application was developed in 2023 using the Design Thinking method. This prototype was tailored to the needs of pregnant women and midwives in Indonesia and demonstrated feasibility for initial public use. This study involved collaboration with the Provincial Board of the Indonesian Midwives Association (PD-IBI) of Riau Province. Data was collected through Focus Group Discussions (FGDs) with key midwifery figures and midwives, along with direct surveys of potential users and the community. These efforts produced valuable feedback and recommendations for improving the prototype. The input was gathered to create a new Software Product Line (SPL), laying the foundation for future product development. Utilizing the prototyping method allowed iterative refinement, ensuring alignment with user needs and expectations, particularly for stakeholders unfamiliar with software development. This research produced a validated SPL that is ready for further development and implementation. It contributes to advancing health digitization and improving maternal health monitoring. The refined product can enhance healthcare quality in Riau Province and support broader health practices across Indonesia.